Adaptive layouts for authoring NCL programs - Amorim, Glauco Fiorott; Santos, Joel André Ferreira dos; Muchaluat-Saade, Débora Christina Muchaluat (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2013)
This paper presents a layout module that incorporates the facility of specifying adaptive spatial layouts, providing automatic creation of regions and descriptors for NCL documents. Two types of adaptive spatial layouts are provided: flowLayout and gridLayout. Adaptive layouts are very useful for defining generic templates for hypermedia documents, where the number of components will be specified by the final NCL application. Therefore this proposal facilitates the authoring of hypermedia documents used for interactive content creation in the Brazilian Digital TV System.